Polymorphisms in Pfkelch13 domains before and after the introduction of artemisinin-based combination therapy in Southwest Nigeria - Abiodun Amusan; Olugbenga Akinola; Kazeem Akano; María Hernández-Castañeda; Jenna K. Dick; Akintunde Sowunmi; Geoffrey Hart; Grace Gbotosho (PLoS ONE, 2025)
Emergence of artemisinin resistance in East Africa has greatly necessitated surveillance of artemisinin resistance in other African countries with great malaria burden. Specific mutations within the β-propeller and BTB/Poz domains of Pfkelch13 gene are validated markers of artemisinin resistance. Sparse information exists on mutations outside these domains that may also contribute to artemisinin resistance. This study evaluated the occurrence and frequency of mutations in all domains of Pfkelch13 gene, and their impact on treatment outcome in Ibadan pre- and post-adoption of Artemisinin-based Combination Therapies (ACTs) in Nigeria. Dry blood spots prepared from blood samples obtained from P. falciparum-infected patients during retrospective (2000–2005) and prospective (2021) studies were analysed. Treatment outcomes with dihydroartemisinin-piperaquine were evaluated in a cohort of patients from the prospective study during a 42-day follow-up. Nested amplifications of Pfkelch13 gene fragments were done and subjected to Sanger dideoxy sequencing. Mutations were identified by sequence alignment and correlated with treatment outcome parameters including parasite clearance time (PCT) and day 2 parasite reduction ratio (PRRD2) among others. Mean PCT was 2.1 ± 0.6 days (95%CI: 1.97–2.24) while PRRD2 was 4815 with 100% adequate clinical and parasitological response. Altogether, 64 (11 retrospective/53 prospective) samples were successfully sequenced. None of the β-propeller domain mutations validated as artemisinin resistance markers were found within the analysed samples. However, four distinct mutations, K189T (64.2%), K189N (1.9%), R255K (3.8%), and N217H (1.9%) were identified within the N-terminal domain of the prospective samples while the K189T mutation was identified in a retrospective sample obtained in 2003. The K189T and R255K mutations correlated significantly with longer parasite clearance time in treated patients (P < 0.002). There was no evidence of validated molecular marker of artemisinin resistance within the ß-propeller domain of Pfkelch13. However, frequency of K189T mutation and its significant correlation with longer PCT may suggest possibilities of geographical variations in genetic drivers of artemisinin resistance.